The importance of public discussions in improving the Constitution of the Republic of Uzbekistan - Sherov Quvondiq Polvonnazarovich (Zien Journals, 2023)
This article focuses on constitutional reforms undertaken in the Republic of Uzbekistan, amendments and amendments to the basic law, as well as a new constitutional bill issues such as publicdiscussions. The article outlines scientifically-based proposals and recommendations for the importance of constitutional legislation in public discussions and the further improvement of legislation through foreign experience.
Keywords: Constitution; law; regulatory document; public consultation